Influence of temperature variability on physiological, hematological and biochemical profiles of growing and adult Karan Fries cattle - BHAN, CHANDRA; SINGH, S V; HOODA, O K; UPADHYAY, R C; BEENAM, BEENAM (The Indian Journal of Animal Sciences, 2013)
Temperature variability impact on physiological, hematological and biochemical parameters of growing and adult Karan Fries cattle was studied during hot humid, winter, spring and summer. During forenoon and afternoon the respiration rate (RR) and rectal temperature (RT) increased by 4.67 and 3.67 breaths/min and 0.87°C and 0.77°C respectively in growing KF cows during summer over spring. The respective values increased in adult KF cows to 2.83 and 6.67 breaths/min and 0.79°C and 0.88°C during forenoon and afternoon during summer over spring. Similar pattern of increase in skin temperature (ST) and pulse rate (PR) was observed during summer and hot humid season over the spring season. The hematological parameters, viz. packed cell volume (PCV) and hemoglobin (Hb) were significantly higher during summer compared to other seasons of the year in both groups of animals. The hematological parameters (RBC, WBC, Hb and PCV) were lower during afternoon compared to forenoon in both groups of cattle during different seasons. The plasma enzymes (ALT, AST, ALP, LDH) activity were significantly higher (P<0.05) during summer and hot humid season than spring and winter in both groups. Physiological and biochemical parameters showed positive correlation whereas hemat (THI). Our results indicated significant deviations in different physiological, hematological and biochemical profiles during summer and hot humid season from baseline data (spring). Therefore, these crossbred cattle need to be protected from extreme thermal stress for maintaining the homeothermy/homeostasis specifically during dry and hot humid summer for sustained productivity.